Management of a traumatic avulsion of the right upper lobe bronchus. (August 2022) - Park, Jiwon V.; Williams, Aaron M.; Scott, John W.; Blank, Ross; Reddy, Rishindra M.
Abstract: Tracheobronchial injuries are rare but life-threatening and require early diagnosis, appropriate airway management, and emergent surgical intervention. We report a case of a post-traumatic, isolated avulsion of the right upper lobe bronchus in a 60-year-old woman involved in a pedestrian versus motor vehicle accident. After transfer from an outside hospital with a single lumen endotracheal tube and multiple right sided chest tubes with large air leaks, the patient was taken to the OR for bronchoscopy and surgical exploration. Intraoperatively, a complete avulsion of the right upper lobe was noted. Due to the extended time period from original injury and excellent reported functional status, our patient underwent completion lobectomy of the right upper lobe, primary bronchial repair, with an azygous vein flap.